Impact of deep pectoral myopathy on chemical composition and quality parameters of chicken breast fillet - Giampietro-Ganeco, Aline (2021)
One of the current myopathies affecting the chicken meat industry is deep pectoral myopathy (DPM), also known as green muscle disease or Oregon disease, the condition is considered a major problem in poultry processing lines. Thus, the present study proposes to examine the meat quality of the Pectoralis major muscle (breast fillet) from carcasses of broilers affected by DPM in Pectoralis minor muscle (tender) and from a control group. Breast fillets samples were harvested from Ross AP95 broilers that were slaughtered at 42 days of age and were selected to the occurrence of the myopathy (score 2 and score 3) and from a control group without (score 0) the presence of myopathy. Chemical composition, cholesterol, fatty acid profile, pH, color, water-holding capacity, cooking loss, shear force, sarcomere length, and collagen were analyzed in the breast fillet. And with the results it was observed the samples classified as DPM score 2 had a higher moisture and a lower protein percentage. The higher values lipid was found in the samples from broilers affected by DPM. There was no difference (P > 0.05) fatty acid profile only to C10:0, C15:0, C17:0, C20:0, and C18:2c9,t11. Differences were detected (P < 0.05) for the pH, WHC, SF, and sarcomere length of the samples from broilers affected by DPM. The higher pH observed in the samples from birds classified as DPM score 2 and the higher WHC values were observed in the samples affected by DPM (score 2 and 3). The SF (P < 0.05) among samples, with the most tender samples (lower SF values) being those unaffected by the condition DPM (score 0). The dorsal side surface, where the Pectoralis major muscle is in contact with the Pectoralis minor muscle, higher L* values were found in the meat affected by the myopathy. Although deep pectoral myopathy affects the Pectoralis minor muscle of broilers, it can also alter the qualitative characteristics and chemical composition of the breast fillets (Pectoralis major muscle).